FRACTIONATION OF CARBON AND OXYGEN ISOTOPES IN 13C-RICH PALAEOPROTEROZOIC DOLOSTONES IN THE TRANSITION FROM MEDIUM-GRADE TO HIGH-GRADE GREENSCHIST FACIES: A CASE STUDY FROM THE KOLA SUPERDEEP DRILLHOLE - Melezhik V.A.; Fallick A.E.; Smirnov Y.P.; Yakovlev Y.N. (My University, 2003)
Samples from the Kola Superdeep Drillhole (12 262 m), a deep drillhole (1060 m), and from the surface, seaprated by only around 10 km, provided a unique opportunity for direct tracing of delta(13)C and delta(18)O changes through a low- to high-grade greenschist-facies transition within impure, C-13-rich Palaeoproterozoic dolostones. The least-altered dolostones have delta(13)C of +9 parts per thousand and delta(18)O of 22 parts per thousand. The metamorphic transition is expressed by dolomite + calcite, + quartz K-feldspar - tremolite + calcite(2) dolomite calcite, and defined by C-13 depletion of calcite(2) (c. 3.0 parts per thousand), calcite, (1.0-2.0 parts per thousand) and dolomite (<1 parts per thousand) which is associated with a Rayleigh distillation process. delta(18)O shows a considerable resetting in all carbonate components by around 6 parts per thousand caused by a Rayleigh distillation process coupled with isotopic exchange between the carbonates and fluids with an external source of oxygen. The retrograde alteration is expressed by the formation of quartz-chlorite veinlets within tectonically bound zones of brecciated and sheared dolostones. The maximum 180 depletion in dolomite (9 parts per thousand) and calcite(1) (c. 4 parts per thousand) were probably controlled by infiltration into permeable zones of external fluids associated with retrograde alteration; delta(13)C remains largely unaffected.
Keywords: Kola Superdeep Drillhole; Paleoproterozoic; dolomite; calcite; stable isotopes; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская